The Use of Digital Microscopy to Compare the Thicknesses of Normal Corneas and Ex Vivo Rejected Corneal Grafts with a Focus on the Descemet’s Membrane - Taíse Tognon; Sabrina Bergeron; Christina Mastromonaco; Kleyton Barella; Adriano Pasqualotti; Laura Nunez; Francisco Murta; Luciene Barbosa de Sousa; Mauro Campos; Miguel Noel Nascentes Burnier (Journal of Ophthalmology)
Objective. To compare the thickness of corneal layers, specifically the Descemet’s membrane (DM), in normal corneas and in failed grafts due to rejection (FGRs) using the digital histopathology and to propose a model for the measurement of corneal layers using this method. Methods. This is a prospective, cross-sectional study performed at the MUHC-McGill University Ocular Pathology & Translational Research Laboratory (McGill University, Montreal, Canada). Histopathological sections of 25 normal human corneas and 40 FGRs were fully digitalized and examined. Inclusion criteria: samples diagnosed as normal corneas or FGRs, from patients older than 18 years of age. Exclusion criteria: histopathological sections without adequate tissue or missing epidemiological information. For each sample, the thicknesses of the epithelium, stroma, and DM were acquired. From a perpendicular plane of reference, two central measurements and two nasal and two temporal peripheral measurements were obtained. Results. There were differences between the normal and FGR groups in the mean central thickness of the epithelium (p<0.001), the nasal and temporal stromal regions (p<0.001), and of the DM in the nasal and temporal regions (p<0.001). Compared with the extremities of the sample (nasal and temporal), the mean thickness of the DM in normal corneas was lower in the central region (p<0.001), and this difference was not found in the FGR group. Conclusions. Normal corneas have a thinner epithelium in the central region than the FGR group. In addition, the stroma and DM thicknesses of the nasal and temporal periphery were significantly higher in normal corneas than in those from the FGR group. The digital microscopy protocol applied in this study may be useful for further research studies regarding cornea and other tissues.